Internal factors affecting continuous donations among cash Waqf donors - Kassim, Marina; Che Embi, Nor Azizan; Haron, Razali; Ibrahim, Khairunisah (HRMARS, 2019)
Cash waqf has a great potential as one of Islamic innovation financial instrument to alleviate the poverty and increase socio-economic in the society. Studies into the factors contributing to the charity among public or first donation are abound. However, the factors effecting donor continuous donation or repeat donation have not yet received significant attention within the academic community. Therefore, this study aimed to identify the internal factors affecting donor’s motivation to continuous donation among cash waqf donors who are constantly contributing donation through monthly salary deduction. This article postulates that although the factors positively affecting first donation may also impact repeat donation, but the effects of these factors on the two behavioral motivations may vary. The study shows that donor continuous donation is most influenced by donor’s trust to the organizations, familiarity with the cause of organization and perceived efficacy of the contribution. These preliminary study is considered important to develop a clear understanding with regard to further improve the relationship between donors and waqf organizations in Malaysia.